2012
DOI: 10.1002/lary.23749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fellowship training on research productivity in academic otolaryngology

Abstract: Fellowship-trained otolaryngologists had higher h-indices, and faculty members trained in the subspecialties with the highest research productivity were disproportionately represented in positions of leadership within academic otolaryngology, probably reflecting the importance of research contributions in the academic advancement process, although other factors, such as educational contributions and clinical performance, may also be important factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 72 publications
(127 citation statements)
references
References 24 publications
(31 reference statements)
2
117
0
Order By: Relevance
“…Although this certainly is possible, it is important to realize that repeated self-citation would be needed to significantly influence an author's h-index score. 15,16,22 Some also have suggested that being a coauthor on a paper of someone producing significant research output is another route for h inflation, echoing the argument that author order or significance of contributions is not valued with this metric. 5 Although this is certainly a valid point, it should not have a significant effect on an individual's h-index unless the individual is repeatedly a coauthor with someone else who is producing influential research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this certainly is possible, it is important to realize that repeated self-citation would be needed to significantly influence an author's h-index score. 15,16,22 Some also have suggested that being a coauthor on a paper of someone producing significant research output is another route for h inflation, echoing the argument that author order or significance of contributions is not valued with this metric. 5 Although this is certainly a valid point, it should not have a significant effect on an individual's h-index unless the individual is repeatedly a coauthor with someone else who is producing influential research.…”
Section: Discussionmentioning
confidence: 99%
“…6,[15][16][17] Our objectives in the present analysis were to further evaluate whether the relationship between h-index and academic rank persisted among faculty within surgical subspecialties described on the Web site of the American College of Surgeons (ACS) (http://www.facs.org/residencysearch/ specialties/index.html) and to compare these results to those of academic otolaryngologists.…”
Section: Introductionmentioning
confidence: 99%
“…7,10,[14][15][16][17]29,[35][36][37]41,43,52,53,[57][58][59] The Scopus database (www.scopus.com) was used to calculate this bibliometric for the present analysis, as it has been of value in several prior analyses of the h index. 7,18,47,59 One analysis among neurosurgeons found a high degree of correlation between results from the Scopus database and Google Scholar, another commonly used h index resource.…”
Section: Methodsmentioning
confidence: 99%
“…These issues and other potential limitations of the h index have been widely reported in the literature. 3,7,9,10,[12][13][14][15]18,23,25,26,[28][29][30]35,[39][40][41] Despite these known limitations, the h index is an objective measure that takes into account the frequency with which a faculty member has had an impact upon scholarly discourse within a field and has been shown in many analyses to have a strong association with academic promotion, receiving external funding, graduate medical education, and a variety of other factors measuring achievement.…”
Section: Discussionmentioning
confidence: 99%
“…The h index is a bibliometric whose use has been previously described among academic physicians in neurological surgery as well as in other specialties. 6,7,9,10,12,21,[23][24][25][26][27]29,31,32,[35][36][37][38][39][40] It has been shown to have a strong association with scholarly impact, academic advancement, National Institutes of Health (NIH) funding procurement, and other measures of scholarly productivity. It is a widely accessible and easily calculable measure that indicates the degree to which an author is frequently cited on a regular basis, throughout his or her body of work (rather than disproportionate citation of a single work).…”
mentioning
confidence: 99%